“Turun” as Participatory Budgeting Practices based on Siri’ Na Pesse at the Death Ceremony in Baebunta, North Luwu Regency, Indonesia - Tenrigau, Andi Mattingaragau; Dahlan, Herawati; Aida, Nur (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
This study aims to determine participatory budgets of siri’ na pesse in “turun” tradition of death events in Baebunta, Luwu Utara Regency. The study uses an interpretive paradigm with a methodological and ethnographic study of siri’ na pesse. The results show that "turun" is as a participation form of to maega (society) in mobilizing a budget based on a sense of pesse (empathy) and siri’ (shame). The budget mobilization process consists of three parts, namely planning, determining sources, and budget allocation. The first part begins with an internal meeting of the bereaved and relative families; secondly, determining the almost-equally-divided source of the budget; thirdly, the budget allocation to finance the funeral procession and the night of takziah (condolence). The ativities properly shows the upright siri’ (self-esteem) for the bereaved family.